(untitled) (Boletín de la Sociedad Zoológica del Uruguay, 2022)
In this note we reported a Hydrodynastes gigas specimen captured in the year 2006, in Bella Unión, Artigas department. This is the second record in the country and makes it possible to confirm the presence in Uruguay.